Karakteristik pasien skabies di SMF ilmu kesehatan kulit dan kelamin RSUP H. Adam Malik Medan periode Januari 2010-Desember 2012 - Sufina F Nasution; Chairiyah Tanjung; Salia Lakswinar (Fakultas Kedokteran USU, 2012)
Background: Scabies is a highly transmitted disease caused by Sarcoptes scabiei mite. The prevalence and complication which can occur has made scabies a significant public health problem in the developing countries. Objective : To find out the characteristics of scabies patients in the Dermatology and Venereology department at Haji Adam Malik general hospital Medan, in the period of January 2010-December 2012 on scabies epidemiology so that any measures for the improvement of handling patients in the future can be taken.Method : The research was a descriptive study, using secondary data analysis from medical records of scabies patients who visited the Dermatology and Venereology department at Haji Adam Malik general hospital Medan, in the period of January 2010-December 2012.Results : The characteristics of scabies patients were generally males (59.4%), 11 to 15 years old (28.3%), no/pre-school/elementary school graduates (47.1%), students (55.1%). There were 138 scabies patients who visited the Dermatology and Venereology department at Haji Adam Malik general hospital Medan, in the period of January 2010-December 2012.. The clinical charactheristics of scabies were all of the patients had subjective symptoms of pruritus (100%), the morphology of most of the lesion was papules (87.7%), and the location of most of the lesion was on legs (39.9%).Conclusion : The characteristics of scabies patients in the Dermatology and Venereology department at Haji Adam Malik general hospital Medan, were generally males, 11 to 15 years old, no/pre school/Elementary School graduates, students. There were 138 scabies patients who visited the Dermatology and Venereology department at Haji Adam Malik general hospital Medan, in the period of January 2010-December 2012.. The clinical charactheristics of scabies were all of the patients had subjective symptoms of pruritus, the morphology of most of the lesion was papules, and the location of most of the lesion was on legs.Keywords : scabies; characteristics